«Людина науки, закохана в неї...» (М.І.Костомаров) - Гончар, О.Т. (Український історичний журнал, 2007)
До уваги читача подаються маловідомі спогади П.В.Бикова про М.І. Костомарова. Аналізуються місце М.І. Костомарова в суспільно-політичних та наукових процесах другої половини ХІХ ст., особливості його творчої спадщини і змістова цінність мемуарів у цьому сенсі. Little known memoirs of P.V.Bykov about M.I.Kostomarov are presented for reader’s attention. The article analyzes the place of M.I.Kostomarov in social, political and scientific processes of the second half of the XIX century, peculiarities of his creative heritage and the matter value of memoirs in this sense.